Multifunctional composite adhesive film, its preparation method and application
Patent Information
- Application Number
- CN202310062092.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-16
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-01-16
AI Technical Summary
但是,该胶膜的耐老化性能有待进一步提高,
[0065]本发明的多功能复合胶膜,与HJT电池片的粘结性能好,层压后无阴影,TC200后组件功率衰减小。具体的,本发明的多功能复合胶膜,与HJT电池片剥离力为64.8-83.9N/cm,层压后无阴影,TC200后无明显阴影,TC200后组件功率衰减0.98-1.73%,组件功率为618-622w,及经UV60kwh后组件功率为610-613w。
Smart Images

Figure BDA0004061370890000111 
Figure BDA0004061370890000121 
Figure BDA0004061370890000131
Abstract
Description
Technical Field
[0001] This invention relates to the field of adhesive film technology, and in particular to a multifunctional composite adhesive film, its preparation method, and its application. Background Technology
[0002] HJT (Heterojunction with Intrinsic Thin Film) is an N-type monocrystalline bifacial solar cell. It boasts advantages such as simple manufacturing process, high power generation, and low cost per kilowatt-hour, gradually becoming a research hotspot in the photovoltaic industry. HJT cells are made by depositing amorphous silicon thin films on crystalline silicon. The structure of HJT cells can improve the performance of the PN junction, thereby increasing conversion efficiency and open-circuit voltage.
[0003] Although HJT solar cells have high power generation efficiency, they also have certain defects, such as: (1) solar cells are easily damaged by UV light, which affects the power generation efficiency of the entire module; (2) the surface of the solar cells is metal oxide without coating, which has poor adhesion to conventional encapsulation films, and the film is prone to delamination from the solar cells during the aging process; (3) the solar cells themselves are not resistant to high temperatures, so they cannot be prepared by traditional welding methods. Low-temperature silver paste is required for low-temperature string welding; the corresponding low-temperature solder ribbon is expensive; (4) the amount of silver used in the main grid of HJT solar cells is relatively high, and the overall price is expensive.
[0004] CN110713803B discloses a thermoplastic photovoltaic module encapsulating film and its preparation method. The film includes a gas barrier layer and an adhesive layer formed on the upper and lower surfaces of the gas barrier layer. The adhesive layer is composed of 100 parts by weight of a first photovoltaic matrix resin, 0.1-1 parts by weight of a tackifier, 0.1-3 parts by weight of a crosslinking agent, 0-50 parts by weight of a pigment, and 0-3 parts by weight of a processing aid. The first photovoltaic matrix resin is composed of 5-50 parts by weight of ethylene-vinyl acetate resin, 15-95 parts by weight of a modified polyolefin transparent resin, and 0-35 parts by weight of a polyolefin transparent resin. The thermoplastic photovoltaic module encapsulating film has a pre-crosslinking degree of 1-50%. Because it does not contain a crosslinking agent, crosslinking within the screw during extrusion processing can be avoided, significantly increasing production speed. The processing technology is simple, and the production efficiency is high. When applied to photovoltaic modules, it exhibits good weather resistance. However, when this encapsulating film is used in the preparation of HJT solar cells, the adhesion between the film and the solar cell, the module power, and the aging resistance need to be further improved.
[0005] CN112980340A discloses an encapsulating film for encapsulating HJT cells, its preparation method, and the resulting photovoltaic module. The encapsulating film for encapsulating HJT cells includes an adhesive layer and an EVA layer. The adhesive layer is mainly composed of the following components by weight: 100 parts of a base resin, 5-10 parts of a modified resin, and 1-5 parts of additives. The modified resin is mainly prepared by reacting the base resin, initiator, and binder monomers. This invention introduces a specific modified resin into the adhesive layer, adapting the adhesive-enhancing mechanism of the encapsulating film to the composite ITO anti-reflection layer on the HJT surface, achieving complete adhesion between the film and the heterojunction cell, and improving the peel strength between the film and the HJT cell. Simultaneously, the EVA layer exhibits strong peel strength to tempered glass or backsheet surfaces, improving the long-term reliability and service life of the HJT module. However, the aging resistance of this film needs further improvement. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a multifunctional composite film, its preparation method, and its applications. This multifunctional composite film improves the overall heat resistance of the film, reduces film flow during lamination, ensures smooth module production without prior stringing processes, prevents the film from seeping between the solder ribbon and the solar cells, thus avoiding impact on module power generation, and simultaneously fixes the solder ribbon, ensuring the long-term reliability and stability of the module. It can absorb ultraviolet light and convert it into visible light that does not damage the solar cells, reducing UV damage to the cells and improving solar energy utilization efficiency, thereby increasing module power generation.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] A multifunctional composite adhesive film includes an adhesive film layer and a battery cell adhesive layer. The battery cell adhesive layer is a single-layer structure or a double-layer structure. When the battery cell adhesive layer is a double-layer structure, it includes a battery cell surface adhesive layer and an adhesive film surface adhesive layer. The battery cell surface adhesive layer of the battery cell adhesive layer is grafted and modified. The adhesive film layer contains a UV light transfer agent.
[0009] The multifunctional composite adhesive film of the present invention reduces the fluidity of the adhesive film during the lamination process by adding a cell bonding layer with higher heat resistance, ensuring that the module can be produced smoothly without the previous stringing process. The adhesive film will not seep into the space between the solder ribbon and the cell, thus affecting the power generation of the module. At the same time, it fixes the solder ribbon, ensuring the reliability and stability of the module for long-term use.
[0010] It should be noted that the multifunctional composite film of the present invention refers to a film that further improves the overall heat resistance of the film and reduces the flowability of the film during the lamination process; it can absorb ultraviolet light and convert ultraviolet light into visible light that does not damage the solar cells, thereby reducing the damage of ultraviolet light to the solar cells and improving the utilization efficiency of sunlight, thus increasing the power generation of the module.
[0011] The adhesive film layer may be a single-layer adhesive film layer or a multi-layer adhesive film layer. When the adhesive film layer is a single-layer adhesive film layer, it contains the following components by weight:
[0012] The main resin has a weight of 100 parts.
[0013] The main crosslinking agent is 0.2-1 parts by weight, for example, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, etc.
[0014] The crosslinking agent is present in a weight ratio of 0.4-1.5 parts, for example, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, etc.
[0015] The coupling agent is present in parts by weight of 0.1-0.6, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, etc.
[0016] The UV light transfer agent is present in parts by weight of 0-0.5 parts, such as 0, 0.1, 0.2, 0.3, 0.4, 0.5, etc.
[0017] The UV absorber is present in parts by weight of 0-0.5 parts, for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, etc.
[0018] The anti-aging agent is present in parts by weight of 0.1-0.4 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, etc.
[0019] When the adhesive film layer is a multilayer adhesive film layer, it includes a glass surface adhesive film layer and a battery surface adhesive film layer;
[0020] Preferably, the glass adhesive film layer comprises the following components in parts by weight:
[0021] The main resin has a weight of 100 parts.
[0022] The main crosslinking agent is 0.5-1 parts by weight, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, etc.
[0023] The crosslinking agent is present in parts by weight of 0.5-1.5, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, etc.
[0024] The coupling agent is present in parts by weight of 0.1-0.6, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, etc.
[0025] The UV light transfer agent is present in parts by weight of 0.1-0.3 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, etc.
[0026] The anti-aging agent is present in parts by weight of 0.1-0.3 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, etc.
[0027] Preferably, the battery surface adhesive film layer comprises the following components in parts by weight:
[0028] The main resin has a weight of 100 parts.
[0029] The main crosslinking agent is 0.5-1 parts by weight, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, etc.
[0030] The crosslinking agent is present in parts by weight of 0.5-1.5, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, etc.
[0031] The coupling agent is present in parts by weight of 0.1-0.6, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, etc.
[0032] The UV absorber is present in parts by weight of 0.1-0.3 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, etc.
[0033] The anti-aging agent is present in parts by weight of 0.1-0.3 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, etc.
[0034] In this invention, the adhesive film layer primarily serves an encapsulation function, while also functioning as a UV light converter and UV light blocker. The adhesive film layer can be a conventional encapsulation film, but to enhance the light conversion and blocker functions, the additive system needs to be adjusted accordingly. The overall thickness of the adhesive film layer can be 200-800 μm as needed, for example, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, or 800 μm.
[0035] In the adhesive film layer, the main resin is any one or a mixture of at least two of the following: ethylene copolymer, polyvinyl butyral, silane-grafted ethylene copolymer, ethylene-methacrylic acid ionomer, or liquid silicone.
[0036] Preferably, the main crosslinking agent comprises any one or a mixture of at least two of the following: tert-butyl peroxide (TBEC), tert-amyl peroxide (TAEC), dicumyl peroxide (DCP), and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.
[0037] Preferably, the co-crosslinking agent comprises any one or a mixture of at least two of triallyl isocyanurate (TAIC), trimethylolpropane triacrylate (TMAIC), trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), or pentaerythritol triacrylate (PETA), ethoxylated trimethylolpropane triacrylate (ethoxylated TMPTA), propoxylated trimethylolpropane triacrylate (propoxylated TMPTA).
[0038] Preferably, the coupling agent comprises any one or a mixture of at least two of the following: 3-methacryloyloxypropylmethyltrimethoxysilane, 3-glycidylpropyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, triisostearoyl titanate isopropyl, isopropyltris(dioctylpyrophosphate)titanate, isocyanate-propyltrimethoxysilane, isocyanate-propyltriethoxysilane, and 1,3,5-tris(trimethoxysilylpropyl)isocyanurate.
[0039] Preferably, the UV light transfer agent comprises any one or a mixture of at least two of the following: organic fluorescent pigments, rare earth organic complexes, rare earth inorganic compounds, CdSe quantum dots, or perovskite quantum dots.
[0040] Preferably, the UV absorber comprises any one or a mixture of at least two of the following: benzophenone UV absorbers, benzotriazole UV absorbers, salicylates UV absorbers, substituted acrylonitrile UV absorbers, and triazine UV absorbers.
[0041] Preferably, the anti-aging agent comprises any one or a mixture of at least two of phenolic antioxidants, phosphite antioxidants, and hindered amine light stabilizers.
[0042] By weight, the cell adhesive layer comprises the following components:
[0043] The main resin has a weight of 100 parts.
[0044] The initiator is in the form of 0.05-0.3 parts by weight, for example, 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, etc.
[0045] The silane is present in parts by weight of 0.5-4 parts, for example, 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, etc.
[0046] The anti-aging agent is present in parts by weight of 0.1-0.5, for example, 0.1, 0.2, 0.3, 0.4, 0.5, etc.
[0047] By weight, the adhesive film layer comprises the following components:
[0048] The main resin has a weight of 100 parts.
[0049] The anti-aging agent is present in parts by weight of 0.1-1 parts, such as 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, etc.
[0050] The cell bonding layer solves problems such as insufficient adhesion and aging-related delamination between the high-heat-resistant resin and the cell substrate. Furthermore, the grafted modification of the bonding layer further enhances its adhesion and long-term aging resistance. The cell bonding layer comprises a cell-side bonding layer and an adhesive film-side bonding layer. Its main function is to ensure sufficient adhesion between the solder ribbon and the cell during lamination, while preventing the adhesive film layer from entering between the solder ribbon and the cell and affecting conductivity. This layer also serves as the adhesive layer to the cell, thus contributing to the overall high adhesion between the product and the cell. The thickness can range from 80-120μm, for example, the thickness of the cell bonding layer is 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm, and 120μm.
[0051] In the battery cell adhesive layer, the main resin is POE.
[0052] Preferably, the initiator is any one or a mixture of at least two of the following: 2-ethylhexyl tert-butyl peroxide (TBEC), tert-amyl peroxide (TAEC), dicumyl peroxide (DCP), and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.
[0053] Preferably, the silane coupling agent is any one or a mixture of at least two of the following: 3-methacryloyloxypropylmethyltrimethoxysilane, 3-glycidylpropyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, triisostearoyl titanate isopropyl, isopropyltris(dioctylpyrophosphate)titanate, isocyanate-propyltrimethoxysilane, isocyanate-propyltriethoxysilane, and 1,3,5-tris(trimethoxysilylpropyl)isocyanurate, preferably vinyltrimethoxysilane. The defined range is consistent with the defined range of the adhesive film layer. After grafting modification with the silane coupling agent, the peel force between the battery surface and the battery cell is improved, while the flowability of the resin is reduced.
[0054] Preferably, the anti-aging agent is any one or a mixture of at least two of the following: phenolic antioxidant (BHT), phosphite antioxidant, and hindered amine light stabilizer.
[0055] In the adhesive layer of the film, the resin is any one or a mixture of at least two of PE, PP and PE-g-PA.
[0056] Preferably, the anti-aging agent is any one or a mixture of at least two of the following: phenolic antioxidants (BHT), phosphite antioxidants, and hindered amine light stabilizers.
[0057] The adhesive film layer is a single layer or multiple layers. Preferably, the thickness of the adhesive film layer is 200-800μm, such as 200μm, 300μm, 400μm, 500μm, 600μm, 700μm, 800μm, etc.
[0058] The cell adhesive layer can be a single-layer or double-layer structure. When it is a double-layer structure, the side in contact with the cell is the cell adhesive layer and the side in contact with the adhesive film is the adhesive film adhesive layer. When it is a single-layer structure, the above distinction is not made.
[0059] When the battery cell bonding layer is a single-layer structure, its thickness is 80-120μm, for example, 80μm, 90μm, 100μm, 110μm, 120μm, etc.
[0060] When the battery cell adhesive layer has a double-layer structure, the thickness of the battery cell surface adhesive layer is 40-60μm, for example, 40μm, 45μm, 50μm, 55μm, 60μm, etc.; the thickness of the adhesive film surface adhesive layer is 40-60μm, for example, 40μm, 45μm, 50μm, 55μm, 60μm, etc.
[0061] The second objective of this invention is to provide a method for preparing the multifunctional composite film described in the first objective. First, a graft-modified raw material is prepared by melt grafting. Then, a battery cell bonding layer is prepared by single-layer or double-layer co-extrusion casting. Finally, during the casting process of the film layer, the battery cell bonding layer and the film layer are bonded together to obtain the multifunctional composite film.
[0062] Preferably, the grafting modification process of the battery cell adhesive layer is as follows: the coupling agent is sprayed into the main resin within 1-4 hours, stirred for 1-4 hours, and after the coupling agent is completely absorbed, it is added into the granulator and grafted granulation is carried out under the processing conditions of 100-280℃. After the grafted granulation is completed, the particles are mixed with the initiator and anti-aging agent and then directly cast into a film.
[0063] A third objective of this invention is to provide an application of the multifunctional composite film described in one objective, using the multifunctional composite film in the preparation of HJT batteries.
[0064] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0065] The multifunctional composite adhesive film of this invention exhibits good adhesion to HJT solar cells, exhibits no shadowing after lamination, and shows minimal power attenuation in the module after TC200 treatment. Specifically, the multifunctional composite adhesive film of this invention has a peel strength of 64.8-83.9 N / cm with HJT solar cells, exhibits no shadowing after lamination, shows no significant shadowing after TC200 treatment, and shows a power attenuation of 0.98-1.73% in the module after TC200 treatment, resulting in a module power of 618-622 W, and a module power of 610-613 W after UV treatment for 60 kWh. Detailed Implementation
[0066] The technical solution of the present invention will be further illustrated below through specific embodiments.
[0067] Unless otherwise specified, all raw materials used in this invention are commercially available or can be prepared using conventional methods in the art.
[0068] Example 1
[0069] The multifunctional composite film of this embodiment includes a film layer with a thickness of 400 μm and a battery cell adhesive layer with a thickness of 90 μm, and the specific composition is shown in Table 1.
[0070] The multifunctional composite film of this embodiment is prepared by the following method:
[0071] First, graft-modified raw materials are prepared by melt grafting. Then, a battery cell bonding layer is prepared by single-layer or double-layer co-extrusion casting. Finally, during the casting process of the adhesive film layer, the battery cell bonding layer and the adhesive film layer are combined to obtain a multifunctional composite adhesive film.
[0072] The specific process of grafting modification of the battery cell adhesive layer is as follows: the coupling agent is sprayed into the main resin within 3 hours, stirred for 3 hours, and after the coupling agent is completely absorbed, it is added into the granulator and grafted granulation is carried out under the processing conditions of 260℃. After the grafted granulation is completed, the particles are mixed with the initiator and anti-aging agent and then directly cast into a film.
[0073] Examples 2-7
[0074] The specific composition of the multifunctional composite films in Examples 2-7 is shown in Table 1. The preparation method of this example is the same as that of Example 1.
[0075] Comparative Example 1
[0076] The difference between this comparative example and Example 1 is that it contains only a film layer and no adhesive layer; everything else is the same as in Example 1.
[0077] Comparative Example 2
[0078] The difference between this comparative example and Example 1 is that the adhesive layer was not modified by grafting with a coupling agent. The specific composition is shown in Table 1, and the preparation method is the same as in Example 1.
[0079] Comparative Example 3
[0080] The difference between this comparative example and Example 1 is that the film layer does not contain UV light transfer agent. The specific composition is shown in Table 1, and the preparation method is the same as in Example 1.
[0081] The specific EVA model is Hanwha EV282, the POE is Dow 38660, the main crosslinking agent-1 is TBEC (Arkema), the main crosslinking agent-2 is TAEC (Arkema), the co-crosslinking agent-1 is TAIC (Hunan Minhe), the coupling agent is 3-methacryloyloxypropylmethyltrimethoxysilane (Kestda), vinyltrimethoxysilane (Kestda), the initiator is Bis25 (Arkema), the anti-aging agent is light stabilizer 770 (Suqian Liansheng), the antioxidant is BHT (Suqian Liansheng), the UV absorber is benzotriazole UV absorber (Suqian Liansheng), and the UV light transfer agent is perovskite quantum dots.
[0082] Table 1
[0083]
[0084]
[0085]
[0086] Note that " / " indicates that it was not added.
[0087] The performance of the multifunctional composite films prepared in Examples 1-7 and Comparative Examples 1-3 was tested, and the test results are shown in Table 2.
[0088] The testing methods and standards for each performance indicator are as follows:
[0089] Peel strength: GB / T 29848-2018;
[0090] EL (electroluminescence) test after lamination: IEC 61215 & 61730;
[0091] TC200 followed by EL: IEC 61215 & 61730;
[0092] The tests for module power, module power after UV 60kWh, and module power degradation after TC200 are conducted in accordance with IEC61215 & 61730.
[0093] Table 2
[0094]
[0095]
[0096] As shown in Table 2, the multifunctional composite film of this invention exhibits good adhesion to HJT solar cells, exhibits no shadowing after lamination, and shows minimal power attenuation after TC200 treatment. Specifically, the multifunctional composite film of this invention has a peel strength of 64.8-83.9 N / cm with HJT solar cells, exhibits no shadowing after lamination, shows no significant shadowing after TC200 treatment, and shows a power attenuation of 0.98-1.73% after TC200 treatment, resulting in a module power of 618-622 W. After UV treatment for 60 kWh, the module power is 610-613 W.
[0097] Comparative Example 1 contains only an adhesive film layer and no bonding layer, which significantly reduces the peel strength between the adhesive film and the HJT cell, resulting in a large amount of blackening and shadowing after lamination.
[0098] In Comparative Example 2, the adhesive layer was not grafted and modified, which caused a significant decrease in the peel strength between the adhesive film and the HJT solar cell. After lamination, a large amount of shadowing and blackening appeared. After TC200, a large amount of shadowing and blackening appeared. After TC200, the module power decreased significantly. The module power and the module power after UV treatment of 60kWh both decreased.
[0099] Comparative Example 3, without the addition of a light transfer agent, resulted in a relatively low power output even though the initial component could be fabricated.
[0100] This invention illustrates the detailed process equipment and process flow through the above embodiments. However, this invention is not limited to the detailed process equipment and process flow described above, meaning that this invention does not necessarily depend on the detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of raw materials for the product of this invention, addition of auxiliary components, and selection of specific methods, all fall within the protection scope and disclosure scope of this invention.
[0101] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0102] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0103] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A multifunctional composite adhesive film, characterized in that, It includes an adhesive film layer and a battery cell bonding layer. The battery cell bonding layer has a double-layer structure, including a battery cell surface bonding layer and an adhesive film surface bonding layer. The battery cell surface bonding layer of the battery cell bonding layer is grafted and modified. The adhesive film layer contains a UV light transfer agent. The adhesive film layer is a multi-layer adhesive film layer, including a glass surface adhesive film layer and a battery surface adhesive film layer; By weight, the glass adhesive film layer comprises the following components: 100 parts of main resin 0.5-1 part of main crosslinking agent 0.5-1.5 parts of crosslinking agent 0.1-0.6 parts of coupling agent 0.1-0.3 parts UV light transfer agent Anti-aging agent 0.1-0.3 parts; The main resin in the glass adhesive film layer is EVA; By weight, the battery surface adhesive film layer comprises the following components: 100 parts of main resin 0.5-1 part of main crosslinking agent 0.5-1.5 parts of crosslinking agent 0.1-0.6 parts of coupling agent 0.1-0.3 parts UV absorber Anti-aging agent 0.1-0.3 parts; The main resin of the battery surface adhesive film layer is POE; By weight, the battery cell adhesive layer comprises the following components: 100 parts of main resin Initiator 0.05-0.3 parts 0.5-4 parts of silane coupling agent Anti-aging agent 0.1-0.5 parts; The main resin of the battery cell adhesive layer is PE; By weight, the adhesive film surface layer comprises the following components: 100 parts of main resin Anti-aging agent 0.1-1 part; The main resins of the adhesive film surface layer are PE and PP; The multifunctional composite film is prepared by the following method, which includes the following steps: First, a graft-modified raw material is prepared by melt grafting, and a battery cell bonding layer is prepared by double-layer co-extrusion casting. Then, during the casting process of the adhesive film layer, the battery cell bonding layer and the adhesive film layer are combined to obtain the multifunctional composite adhesive film. The grafting modification process of the battery cell adhesive layer is as follows: the coupling agent is sprayed into the main resin within 1-4 hours, stirred for 1-4 hours, and after the coupling agent is completely absorbed, it is added to the granulator and grafted granulation is carried out under the processing conditions of 100-280℃. After the grafted granulation is completed, the particles are mixed with the initiator and anti-aging agent and then directly cast into a film.
2. The multifunctional composite film according to claim 1, characterized in that, The main crosslinking agent comprises any one or a mixture of at least two of the following: 2-ethylhexyl carbonate tert-butyl peroxide, (2-ethylhexyl) carbonate tert-amyl peroxide, dicumyl peroxide, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.
3. The multifunctional composite film according to claim 1, characterized in that, The co-crosslinking agent comprises any one or a mixture of at least two of the following: triallyl isocyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, or pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, and propoxylated trimethylolpropane triacrylate.
4. The multifunctional composite film according to claim 1, characterized in that, The coupling agent comprises a silane coupling agent and / or an isocyanate coupling agent.
5. The multifunctional composite film according to claim 1, characterized in that, The UV light transfer agent comprises any one or a mixture of at least two of the following: organic fluorescent pigments, rare earth organic complexes, rare earth inorganic compounds, CdSe quantum dots, or perovskite quantum dots.
6. The multifunctional composite film according to claim 1, characterized in that, The UV absorber comprises any one or a mixture of at least two of the following: benzophenone UV absorbers, benzotriazole UV absorbers, salicylates UV absorbers, substituted acrylonitrile UV absorbers, and triazine UV absorbers.
7. The multifunctional composite film according to claim 1, characterized in that, The anti-aging agent comprises any one or a mixture of at least two of the following: phenolic antioxidants, phosphite antioxidants, and hindered amine light stabilizers.
8. The multifunctional composite film according to claim 4, characterized in that, The silane coupling agent comprises any one or a mixture of at least two of the following: 3-methacryloyloxypropylmethyltrimethoxysilane, 3-glycidylpropyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, isopropyl triisostearoyl titanate, and isopropyl tris(dioctylpyrophosphate)titanate.
9. The multifunctional composite film according to claim 4, characterized in that, The isocyanate coupling agent comprises any one or a mixture of at least two of isocyanate-propyltrimethoxysilane, isocyanate-propyltriethoxysilane, and 1,3,5-tris(trimethoxysilylpropyl)isocyanurate.
10. The multifunctional composite film according to claim 1, characterized in that, The initiator is any one or a mixture of at least two of the following: 2-ethylhexyl tert-butyl peroxide, (2-ethylhexyl) tert-amyl peroxide, diisopropylbenzene peroxide, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.
11. The multifunctional composite film according to claim 1, characterized in that, In the battery cell adhesive layer, the silane coupling agent is any one or a mixture of at least two of the following: 3-methacryloyloxypropylmethyltrimethoxysilane, 3-glycidylpropyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, triisostearoyl titanate isopropyl, isopropyltris(dioctylpyrophosphate)titanate, isocyanate-propyltrimethoxysilane, isocyanate-propyltriethoxysilane, and 1,3,5-tris(trimethoxysilylpropyl)isocyanurate.
12. The multifunctional composite film according to claim 1, characterized in that, The thickness of the adhesive film layer is 200-800 μm.
13. The multifunctional composite film according to claim 1, characterized in that, The thickness of the battery cell bonding layer is 80-120 μm.
14. The multifunctional composite film according to claim 1, characterized in that, When the battery cell adhesive layer has a double-layer structure, the thickness of the adhesive layer on the battery cell side is 40-60 μm, and the thickness of the adhesive film side adhesive layer is 40-60 μm.
15. A method for preparing a multifunctional composite film as described in any one of claims 1-14, characterized in that, Includes the following steps: First, a graft-modified raw material is prepared by melt grafting, and a battery cell bonding layer is prepared by double-layer co-extrusion casting. Then, during the casting process of the adhesive film layer, the battery cell bonding layer and the adhesive film layer are combined to obtain the multifunctional composite adhesive film. The grafting modification process of the battery cell adhesive layer is as follows: the coupling agent is sprayed into the main resin within 1-4 hours, stirred for 1-4 hours, and after the coupling agent is completely absorbed, it is added to the granulator and grafted granulation is carried out under the processing conditions of 100-280℃. After the grafted granulation is completed, the particles are mixed with the initiator and anti-aging agent and then directly cast into a film.
16. An application of the multifunctional composite film as described in any one of claims 1-14, characterized in that, The multifunctional composite film is used in the preparation of HJT batteries.
Citation Information
Patent Citations
A thermoplastic photovoltaic module encapsulating film and its preparation method
CN110713803B
Packaging adhesive film for packaging HJT battery, preparation method of packaging adhesive film and prepared photovoltaic module
CN112980340A
Contraceptive implant
IE61730B1
UV light conversion packaging adhesive film and preparation method thereof
CN114958215A
